Pembelajaran Berbasis Kritik Sastra untuk Mengembangkan Kemampuan Interpretatif Siswa di SMP Unismuh Makassar - Ulviani, Maria; Rimang, Siti Suwadah; Haslinda, Haslinda; Kemala, Rosmalina (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2026)
This study aims to describe the implementation of literary criticism-based instruction (LCBI) in literature learning and to analyze its effect on students’ interpretative skills at SMP Unismuh Makassar. The research employed a qualitative descriptive approach through a two-cycle classroom action research design involving 28 eighth-grade students selected purposively. Data were collected through observation, interviews, field notes, and document analysis, and analyzed interactively using data reduction, display, and conclusion drawing. The findings revealed that LCBI significantly improved students’ interpretative ability, as indicated by the increase in the average score from 63.4 in the pre-cycle to 85.3 in the second cycle. Improvements were evident in students’ abilities to interpret implicit meanings, analyze structure and style, and construct logical interpretative arguments. Moreover, the approach fostered active participation, confidence, and reflective engagement with literary texts. It can be concluded that literary criticism-based instruction effectively enhances students’ interpretative and critical thinking skills while offering a humanistic, reflective, and contextual model for literature learning in secondary education.